Characteristics of the Labi-labi Habitat (Amyda cartilaginea) in the Tawun Ngawi Tourism Park - Lutfiana Rahma Nurjanah; Sukarsono Sukarsono; Husamah Husamah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Labi-labi is a type of soft shell turtle that lives in fresh water. Labi-Labi is also a semi-aquatic animal that often spends its life in the waters. The population of turtles in the wild is widely used by the community for sale or consumption. Therefore, over time, people made conservation efforts to prevent the extinction of the turtles. One of the turtle conservation is the Tawun Ngawi Tourism Park. This tourist park is one of the conservation of the turtles and also the artificial habitat of the turtles. As a place for the conservation of turtles, of course the Tawun Tourism Park must be in accordance with the natural habitat of the turtles. The existence of this study aims to determine the characteristics and suitability level of the artificial habitat in the Tawun Tourism Park area. Then the method of conducting this research was carried out by direct observation by measuring the existing biotic and abiotic parameters and analyzed according to the suitability of their natural habitat. So that the result is that the artificial habitat in the Tawun Ngawi Tourism Park has characteristics that are in accordance with the natural habitat of the turtles. Then the hope for further research needs to be explored further regarding the habitat characteristics of the labi-labi in the wild.